Minimal change disease with concurrent thin basement membrane disease: A case report - Alroshodi, Abdulaziz I. (International Journal of Health Sciences, 2020)
Minimal change disease (MCD) is a main cause of the nephrotic syndrome. Thin basement membrane disease (TBMD) is another disease characterized by microscopic hematuria. The present case is a young adult female who presented with classic nephrotic syndrome, but she had microscopic hematuria as well. Hematuria can be part of MCD in 21% of patients, but in this case, histopathological diagnosis confirmed MCD with concurrent TBMD. This was reported only in two cases, up to our literature review. Using steroids resulted in nephrotic syndrome improvement, but microscopic hematuria has persisted, which is mostly related to TBMD rather than a primary part of MCD. Up to our knowledge, this is the first case report of MCD with concurrent TBMD in Arab countries.